The Diagnosis of Protein Energy Wasting in Chronic Peritoneal Dialysis Patients Is Influenced by the Method of Calculating Muscle Mass. A Prospective, Multicenter Study - Roth-Stefanski, Cristina Techy; Rodrigues de Almeida, Naiane; Biagini, Gilson; Scatone, Natália K.; Nerbass, Fabiana B.; de Moraes, Thyago Proença (Frontiers in Medicine, 2021)
Objective: To analyze the concordance and the agreement between bioimpedance spectroscopy (BIS) and anthropometry for the diagnosis of protein energy wasting (PEW) in chronic peritoneal dialysis patients. Methods: Prospective, multi-center, observational study using multifrequency bioimpedance device (BCM®) and anthropometry for the diagnosis of PEW as recommended by International Society of Renal Nutrition and Metabolism (ISRNM). The Cohen’s kappa was the main test used to analyze concordance and a Bland-Altmann curve was built to evaluate the agreement between both methods. Results: We included 137 patients from 3 PD clinics. The mean age of the study population was 57.7±14.9, 47.8% had diabetes, and 52.2% were males. We calculated the scores for the diagnosis of PEW at 3 and 6 months and in average 40% of the study population were diagnosed with PEW. The concordance in the diagnosis of PEW was only moderate between anthropometry and BIS at both T3 and T6. The main factor responsible to our results was a low to moderate correlation for muscle mass in kilograms, with a R2 of 0.35. The agreement was poor, with a difference of more than 10kg of muscle mass on average and with more than a quarter of all cases beyond limits of agreements. Conclusion: Current diagnosis of PEW may differ depending on the tools used to measure muscle mass.